Left ventricle size quantification using non-contrast-enhanced cardiac computed tomography – association with cardiovascular risk factors and coronary artery calcium score in the general population: The Heinz Nixdorf Recall Study. (August 2015) - Dykun, Iryna; Mahabadi, Amir A; Lehmann, Nils; Bauer, Marcus; Moebus, Susanne; Jöckel, Karl-Heinz; Möhlenkamp, Stefan; Erbel, Raimund; Kälsch, Hagen
Background: Increased left ventricular (LV) size is associated with cardiovascular mortality and morbidity. Once non-contrast cardiac computed tomography (CT) is performed for other purposes, information of LV size is readily available. Purpose: To determine the association of gated CT-derived LV size with cardiovascular risk factors and coronary artery calcification (CAC) and to describe age- and gender-specific normative values in a general population cohort. Material and Methods: LV area was quantified from non-contrast-enhanced CT in axial, end-diastolic images at a mid-ventricular slice in participants of the population-based Heinz Nixdorf Recall Study, free of known cardiovascular disease. LV index (LVI) was calculated by the quotient of LV area and body surface area (BSA). Crude and adjusted regression analyses were used to determine the association of LVI with risk factors and CAC. Results: Overall, 3926 subjects (age 59 ± 8 years, 53% women) were included in this analysis. From quantification in end-diastolic phase, men had larger LV index (2232 ± 296 mm 2 /m 2 vs. 2088 ± 251 mm 2 /m 2, both P  < 0.0001). LVI was strongly correlated systolic blood pressure (men, PE [95% CI]: 22.8 [15.5–30.2] mm 2 /10 mmHg; women, 23.4 [18.1–28.6]), and antihypertensive medication (men, 45.2 [14.7–75.8] mm 2 ; women: 46.5 [22.7–70.2], all P  < 0.005). Cholesterol levels were associated with LVI in univariate analysis, however, correlations were low (R 2  ≤ 0.04). In multivariable regression, blood pressure, antihypertensive medication and cholesterol levels, remained associated with LVI ( P  < 0.05). LVI was linked with CAC in unadjusted (men, increase of CAC + 1 by 13.0% [1.4–25.8] with increased LVI by 1 standard deviation of LVI, P  = 0.03; women, 20.7% [10.0–32.3], P  < 0.0001) and risk factor adjusted models (men, 14.6% [3.7–26.6], P  = 0.007); women, 17.4% [7.8–27.8], P  = 0.0002). Conclusion: Non-contrast cardiac CT derived LV index is associated with body size and hypertension. LVI is weakly linked with CAC-score. Further studies need to evaluate whether assessment of LV dimensions from cardiac CT helps identifying subjects with increased cardiovascular risk.